Exercise Performance and Corticospinal Excitability during Action Observation - Wrightson, James G.; Twomey, Rosie; Smeeton, Nicholas J. (Frontiers in Human Neuroscience, 2016)
Purpose: Observation of a model performing fast exercise improves simultaneous exercise performance, however the precise mechanism underpinning this effect is unknown. The aim of the present study was to investigate whether the speed of the observed exercise influenced both upper body exercise performance and the activation of a cortical action observation network. Method: In Experiment 1, 10 participants completed a 5 km time trial on an arm-crank ergometer whilst observing a blank screen (no-video) and a model performing exercise at both a typical (i.e., individual mean cadence during baseline time trial) and 15% faster than typical speed. In experiment two, 11 participants performed arm crank exercise whilst observing exercise at typical speed, 15% slower and 15% faster than typical speed. In experiment 3, 11 participants observed the typical, slow and fast exercise, and a no-video, whilst corticospinal excitability was assessed using transcranial magnetic stimulation. Results: In Experiment 1 performance time decreased, and mean power increased, during observation of the fast exercise compared to the no-video condition. In Experiment 2, cadence and power increased during observation of the fast exercise compared to the typical speed exercise but there was no effect of observation of slow exercise on exercise behaviour. In Experiment 3, observation of exercise increased corticospinal excitability; however, there was no difference between the exercise speeds. Conclusion: Observation of fast exercise improves simultaneous upper-body exercise performance. However, because there was no effect of exercise speed on corticospinal excitability, these results suggest that these improvements are not solely due to changes in the activity of the action observation network.